The Prodigal Corporation: an Analysis on the Effectiveness of the ACCC's Immunity Policy for Cartel Conduct. (11th June 2013) - Gray, Anthony; Nguyen, Bonnie T.; Wait, Andrew
<x xml:space="preserve">Abstract</x> We examine the impact of the ACCC's leniency policy (Immunity Policy) on cartel stability. The policy, by reducing the fines of the first cartel members who cooperate with competition authorities, can act to deter collusion. However, we find that care is needed in how a leniency policy is implemented. It is possible that the leniency policy can make collusion easier to sustain than in its absence. Further, the ACCC's Cooperation Policy, which applies to all parties who assist the Commission with an investigation, can act to undermine the effectiveness of the leniency policy.